Child injury prevention in the home: A national survey of safety practices and use of safety equipment in deprived families. (January 2014) - Mulvaney, CA; Watson, MC; Smith, S; Coupland, C; Kendrick, D
Objective: To determine the prevalence of home safety practices and use of safety equipment by disadvantaged families participating in a national home safety equipment scheme in England. Design: Cross-sectional postal survey sent to a random sample of 1, 000 families. Setting: England, United Kingdom. Results: Half the families (51%) returned a completed questionnaire. The majority of families (82.3%) reported never drinking hot drinks whilst holding a child and 90.7% reported almost always keeping medicines locked away. High numbers of families reported that they never leave their children in the bath alone (85.7%). Of families with children under one year, 82.1% would never leave the baby on a high surface but only just over half (53.3%) said they never use a baby walker. One-third of families stored cleaning products unsafely in the kitchen or bathroom. Minority ethnic families were significantly less likely to adopt a number of safety practices than white families. Ten per cent of respondents reported that their children had had one or more injuries requiring medical attention in the six months preceding completion of the questionnaire. Conclusions: While the prevalence of many safety practices was high in families, findings regarding the use of baby walkers, storage of cleaning products and the practices of minority ethnic families highlight issues requiring further health education intervention. National surveys such as this one provide key information necessary for planning future strategies.